ogistical Costs: Study in a Transport Company from Santa Catarina (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective(s): Identify the main logistical costs of a transport company in the west of Santa Catarina, from different operating segments. Method(s): This is a descriptive, documental, and qualitative study. Two operating segments of the company under study were analyzed. Results: Variable costs are more representative in the two operations of the company and are composed of: expenses with fuel, maintenance, and tires, representing more than 80% of direct costs and total variables of both operations analyzed and in relation to other costs involved, represent more than 60%. Fuel alone represents 55% of the total cost of the X segment and 54% of the Y segment. As a transport company, all variable expenses are related to the kilometer traveled in the analyzed period. Regarding fixed costs (direct and indirect), the main expense of this group is direct and indirect labor and their respective charges.
Keywords: Costs. Logistic costs. Shipping company. Cost accounting.